Abnormal intracellular calcium homeostasis in sympathetic neurons from young prehypertensive rats - Li, D; Lee, C; Buckler, K; Parekh, A; Herring, N; Paterson, D (2012)
Hypertension is associated with cardiac noradrenergic hyperactivity, although it is not clear whether this precedes or follows the development of hypertension itself. We hypothesized that Ca homeostasis in postganglionic sympathetic neurons is impaired in spontaneously hypertensive rats (SHRs) and may occur before the development of hypertension. The depolarization-induced rise in intracellular free calcium concentration ([Ca]i; measured using fura-2-acetoxymethyl ester) was significantly larger in cultured sympathetic neurons from prehypertensive SHRs than in age matched normotensive Wistar-Kyoto rats. The decay of the [Ca]i transient was also faster in SHRs. The endoplasmic reticulum Ca content and caffeine-induced [Ca]i amplitude were significantly greater in the young SHRs. Lower protein levels of phospholamban and more copies of ryanodine receptor mRNA were also observed in the young SHRs. Depleting the endoplasmic reticulum Ca store did not alter the difference of the evoked [Ca]i transient and decay time between young SHRs and Wistar-Kyoto rats. However, removing mitochondrial Ca buffering abolished these differences. A lower mitochondrial membrane potential was also observed in young SHR sympathetic neurons. This resulted in impaired mitochondrial Ca uptake and release, which might partly be responsible for the increased [Ca]i transient and faster decay in SHR sympathetic neurons. This Ca phenotype seen in early development in cardiac stellate and superior cervical ganglion neurons may contribute to the sympathetic hyperresponsiveness that precedes the onset of hypertension. © 2012 American Heart Association, Inc.